A simulation study on effects of exposure to a combination of pesticides used in an orchard and tuber crop on the recovery time of a vulnerable aquatic invertebrate. (2nd May 2014) - Focks, Andreas; Luttik, Robert; Zorn, Mathilde; Brock, Theo; Roex, Erwin; Van der Linden, Ton; Brink, Paul J. Van den
Abstract The aim of the present study was to assess whether population effects and recovery times increase when a population of a vulnerable aquatic invertebrate is exposed to concentrations of 1 or multiple pesticides. The 2 sets of pesticide combinations tested are typical for orchard and tuber crops in The Netherlands. Exposure concentrations were predicted using the FOCUS step 3 modeling framework and the Dutch drainage ditch scenario. Recovery times were assessed using the MASTEP population model. We simulated the population dynamics and pesticide effects in a Monte Carlo style by using median effective concentration values drawn from an arthropod species sensitivity distribution. In the tuber scenario, exposure to λ‐cyhalothrin resulted in long‐term effects, whereas exposure to the co‐occurring compound fluazinam hardly resulted in (additional) effects. In the orchard scenario, 3 pesticides resulted in large effects just after exposure, but pulse exposures to these compounds did not coincide. The probabilities of effects for the single compounds added up for the combination; in contrast, the recovery times were not higher for the combination compared to those associated with exposure to the individual compounds. The conclusion from the present study's simulations is that exposure to the evaluated pesticide packages may lead to increased mortality probabilities and effect sizes of the combination, but does not lead to longer recovery times for populations with synchronized reproduction than when exposed to the individual compounds. Environ Toxicol Chem 2014;33:1489–1498. © 2013 SETAC